Copal do Brasil: ocorrência e caracterização físico-química da resina jutaicica de Santarém - CORRÊA, João José Lopes (Universidade Federal do Oeste do Pará, 2021)
Jutaicica is the Amazonian colloquial name for the forest product commercially known as ‘copal do Brasil’, a resin that exudes from the trunk of Hymenaea L. (Fabaceae) trees. Species of Hymenaea are distributed in lowland tropical evergreen rainforest in Santarém region, state of Pará. Spectroscopic and thermoanalytical techniques are used in order to characterize and differentiate resin samples. Although copal had been used for centuries in varnish manufacture, it has been completely replaced by synthetic resin in recent decades. This study highlights the need of better understanding and more accurate information regarding ‘copal do Brasil’ occurrence and characterization. Historically, Brazilian domestic market was mainly supplied by the state of Pará, with the resin collected in Santarém and surroundings. Samples from the two main botanical sources, Hymenaea courbaril L. and Hymenaea parvifolia Huber trees were collected along non-flooded land riverside of Tapajós and Curua-Una rivers and their tributaries. Resin batches from the two species can be visually differentiated by naked eye. The H. courbaril material is predominantly clear and light-colored while H. parvifolia ranges from cloudier to darker. Spectra and thermal curves show different patterns allowing a distinction between the two species. The thermal analysis suggests a lower content of polymerized material in H. parvifolia resin. The infrared and carbon 13 nuclear magnetic resonance spectroscopy show homogeneity among the H. courbaril resin samples, but also distinguishes this botanical specie from H. parvifolia resins through the absorption peaks intensity due to olefinic and oxygenated groups.